Visualized Detection of Polyelectrolytes via 1D Photonic Crystals. Issue 2 (25th November 2018) - Wu, Yuxin; Shen, Huaizhong; Zhang, Kai; Zhang, Junhu; Yang, Bai
Abstract: The organic/inorganic hybrid 1D photonic crystal is applied for visible and label‐free detection of charged substances. Exposure to aqueous solutions of various polyelectrolytes alters the swelling ratios of quaternized polymer layers due to the ionic interaction. Visible detection is thus attained along with a shift of the photonic stop band. Especially, by virtue of the diverse degrees and speeds of the shift, polyanions with different concentrations and molecular weights can be differentiated. Likewise, natural polyelectrolytes, such as proteins, have different solution pH values and isoelectric points. Thus, different charged properties yield three kinds of proteins that can be distinguished by the device via reflectance spectra. It is worth noting that biomarkers of illness with different concentrations can also be detected via the naked eye, without any labels. Fortunately, the detection sensitivity basically satisfies the usage requirement. Due to the convenience, flexibility, low power consumption and visibility, the label‐free sensor is suitable for daily life. Abstract : Visible and free‐label detection of charged substances including polyelectrolyte and protein is attained. The varieties of both polyelectrolytes and proteins are differentiated. Meanwhile, the sensor can yield colorful changes toward different concentrations. Besides, polyelectrolytes of different molecular weights are distinguished via the different shift speeds of photonic stop band peak position.